Nonuniqueness of shockwave structures in real gases: the Mach and/or regular reflection - Tarnavsky, G.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2003)
A number of nonuniqueness problems for the shockwave structures arising in high-speed flows at interaction of shocks with the Mach and/or regular reflection are considered. The influence of real gas properties (the effective specific-heat ratio model) on variation in the position of bifurcation points in parameter space (the boundaries of a region where a double solution may exist) is studied.